2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649773
|View full text |Cite
|
Sign up to set email alerts
|

Electrical muscle stimulation for deep stabilizing muscles in abdominal wall

Abstract: Low back pain is associated with dysfunction in recruitment of muscles in the lumbopelvic region. Effective rehabilitation requires preferential activation of deep stabilizing muscle groups. This study was carried out in order to quantify the response of deep stabilizing muscles (transverses abdominis) and superficial muscle in the abdominal wall (external oblique) to electrical muscle stimulation (EMS). Results demonstrate that EMS can preferentially stimulate contractions in the deep stabilizers and may have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
1
14
0
5
Order By: Relevance
“…Previous studies have reported on the ability of transcutaneous NMES applied to the lateral abdominal surface to activate deep lumbar stabilizing muscles [16,17,18,19]. Porcari et al [16] reported significant improvements in muscular strength and endurance of the abdominal region, after applying a belt type NMES to the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported on the ability of transcutaneous NMES applied to the lateral abdominal surface to activate deep lumbar stabilizing muscles [16,17,18,19]. Porcari et al [16] reported significant improvements in muscular strength and endurance of the abdominal region, after applying a belt type NMES to the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromuscular electrical stimulation (NMES) is an effective tool for preferentially stimulating contractions in deep lumbar stabilizers [16,17,18,19,20,21]. Real-time ultrasound imaging (RUSI) is useful for quantifying abdominal and lumbar trunk musculatures, and it has excellent reliability and validity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some methods of physical therapy, including electrical stimulation (ES) (DiMarco and Kowalski 2008), have been used for muscle strengthening (Gerovasili et al 2009). In particular, ES has been adopted to improve not only muscle atrophy, but also impaired motor function in hemiplegic patients (Gerovasili et al 2009) and spinal cordinjured patients (Popovic et al 2006;Popović et al 2009) since the 1980s, and its safety and effectiveness have been confirmed (Gordon and Mao 1994;Hillegass and Dudley 1999;Winslow et al 2003;Coghlan et al 2008;Ochi et al 2010). Furthermore, it was reported that ES of the abdo-men improved the function of the abdominal muscles in tetraplegic patients (DiMarco et al 2008;Lee et al 2008).…”
mentioning
confidence: 99%
“…Some methods of physical therapy, including electrical stimulation (ES), have been used for muscle strengthening. In particular, ES has been adopted to improve not only muscle atrophy but also impaired motor function in hemiplegic patients and spinal cord-injured patients since the 1980s, and its safety and effectiveness have been confi rmed [7][8][9][10][11] . In the present study, we applied surface ES to the abdominal muscles of care-needing elderly people and investigated its effects in motor performance.…”
mentioning
confidence: 99%